2017
DOI: 10.2340/00015555-2473
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability, Validity and Responsiveness of Two Disease Scores (BPDAI and ABSIS) for Bullous Pemphigoid: Which One to Use?

Abstract: A significant obstacle in guiding evidence-based management of bullous pemphigoid (BP) is the lack of a standardised, validated scoring system for the condition. The aim of this study is to evaluate the suitability of the Bullous Pemphigoid Disease Area Index (BPDAI) and the Autoimmune Bullous Skin disorder Intensity Score (ABSIS) as outcome measures for BP in clinical trials. Thirty-two BP patients were repeatedly assessed over four years using Physician Global Assessment (PGA), anti-BP180 ELISA titres, BPDAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 30 publications
5
56
0
Order By: Relevance
“…61 , 62 Comparison of these two BP activity scores showed that BPDAI demonstrated excellent reliability, validity and responsiveness. 63…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…61 , 62 Comparison of these two BP activity scores showed that BPDAI demonstrated excellent reliability, validity and responsiveness. 63…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Pemphigoid and pemphigus are debilitating autoimmune blistering disorders associated with substantial morbidity and morbidity. Patients with bullous pemphigoid or pemphigus usually suffer from intense pain, pruritus and impaired activities of daily living . Patients with pemphigoid and pemphigus have multiple potential risk factors for infections, including epidermal barrier disruption secondary to blistering and erosions, immune dysregulation secondary to cutaneous and/or systemic inflammation, treatment with immunosuppressing agents and comorbid health conditions that are independently associated with infections, such as diabetes…”
Section: Introductionmentioning
confidence: 99%
“…Patients with bullous pemphigoid or pemphigus usually suffer from intense pain, pruritus and impaired activities of daily living. [1][2][3] Patients with pemphigoid and pemphigus have multiple potential risk factors for infections, including epidermal barrier disruption secondary to blistering and erosions, immune dysregulation secondary to cutaneous and/or systemic inflammation, treatment with immunosuppressing agents and comorbid health conditions that are independently associated with infections, such as diabetes. 4 Multiple case series or retrospective studies showed high rates of various infections, some with conflicting results, likely due to low frequency of cases and lack of controls.…”
Section: Introductionmentioning
confidence: 99%
“…Both patients eventually received treatment with intravenous immunoglobulin (IVIG) therapy, which resulted in clinical remission. This clinical improvement with the disappearance of the lesions and a reduction in pruritus was paralleled with a decline in Bullous Pemphigoid Disease Activity Index (BPDAI) activity scores, which is a validated scoring system to measure the related condition, bullous pemphigoid ( Wijayanti et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%